Protective Effect of N-Acetyl Cysteine on Moringa Oleifera Aqueous Leaf Extract-Induced Hepatic Toxicity in Wistar Albino Rats - Agnes, Namaganda; Josephine, Kasolo N; Godfrey, Bbosa S.; Robert, Lukande; Ivan, Kimuli; Godfrey, Katamba; Haruna, Muwonge; Isaac, Okullo; Joshua, Nfambi (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: Moringa oleifera (M. oleifera) is a commonly used medicinal and nutritive plant. The aqueous leaf extract from this plant contains a high concentration of alkaloids and they are toxic to body organs especially the liver leading to hepatotoxicity after long term exposure. However, if N-Acetyl cysteine (NAC) is administered together with M. oleifera extract, it may have a hepatotoxic protective effect. Objective: To establish the protective effect of N-Acetyl cysteine against M. oleifera aqueous leaf extract-induced hepatotoxicity in the Wistar albino rats. Methods: An experimental laboratory-based study conducted at department of Physiology Makerere University, College of Health Sciences. Three treatment groups of six Wistar albino rats each, were dosed intragastrically once a day for 28 days. Group I; negative control, received 8.05g/kg bwt of M. oleifera extract plus 1ml of normal saline (NS), Group II; test group, received 8.05g/kg bwt of M. oleifera extract plus 50mg/kg of NAC. Group III; positive control, received 750mg/kg bwt of Paracetamol plus 50mg/kg of NAC. On the 14th and 29th day, three animals selected randomly from each group were sacrificed; blood samples were collected, the liver was harvested for histopathological analysis. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), bilirubin and total protein levels were determined. Results: There was an increase in serum ALT, AST and ALP levels in the M. oleifera extract plus NS group which was a sign of hepatotoxicity. The M. oleifera extract plus NAC group showed normal serum ALT, AST and ALP levels with no significant changes in the bilirubin (P-value = 0.9089) and total protein levels (P-value = 0.8858). Conclusion: The results have provided evidence that NAC administration with M. oleifera extract effectively prevents the occurrence of M. oleifera leaves xtract- induced hepatotoxicity.